An Analysis of Node/Peer Discovery Approach and Routing Algorithms in Mobile & Traditional Peer-to-Peer Networks - Abdullahi, Mohamed Omar (2012)
Mobile devices are becoming an increasingly indispensable part of people’s everyday life, in the form of mobile phones, PDAs and laptop computers to communicate or share data between them. Centralized client-server networks are being transformed to distributed peer-to-peer networks. Lessons learned from fixed networks have been applied in cellular network. So, there are many challenges faced by traditional and mobile peer-to-peer networks therefore, in this study we examine a comparative analysis of node/peer discovery approach and routing algorithms employed in both traditional and mobile peer-to-peer networks. A qualitative methodology approach was used for data sources. Documents related to node/peer discovery approach and routing algorithms were studied. A comparative method and content analysis were used to analyze the data collected. Findings of the study indicated that there are two clear differences in the aspects of neighboring node/peer discovery approach beside the similarities. The study also showed another differences and similarities in the aspect of routing algorithms. This thesis hopes to offer all necessary useful tips of the divergence on these two aspects and thus to make a contribution allowing researchers to know such divergence.